Job Stress and Workplace Bullying as Correlates of the Physical Health of Civil Servants In Ekpoma, Edo State - Obaze Agbonluae Osumah; Dorcas Edeme-Okonigene (Department of Guidance and Counseling, FIP, Undiksha, 2025)
This study examines work stress and workplace bullying as factors correlated with the physical health of civil servants. Specifically, the study sought to examine job stress and physical health of civil servants in Ekpoma, Edo State. The study made use of the correlational research design. The population of this study covered all the 439 junior and senior civil servants working in the local government council in the study area. A sample of 220workers representing 50 percent of the population was drawn using the stratified random sampling technique. Three instruments were adapted and used in this study. The first instrument is the Job Stress Questionnaire (JSQ), the second is the Workplace bullying Scale (WPBS) while the third is the Physical Health Fitness Questionnaire (PHFQ)”. The instruments were adjudged suitable for use as the cronbach reliability alpha of 0.85, 0.76 and 0.73 were obtained for job stress, workplace bullying and physical health respectively. The Pearson Product Moment Correlation Coefficient (PPMCC) analysis was used to test the entire hypotheses at 0.05 alpha level. The result showed that job stress and workplace bullying have inverse relationship with physical health of the workers. It was recommended that workers need to be periodically trained on stress management and workplace coping behaviours in other to promote their physical health and quality of work life.